Qualitative Exploration of the Feasibility and Acceptability of Workplace-Based Microgrants to Improve Physical Activity: The 10, 000 Steps Pedometer Microgrant Scheme. Issue 8 (August 2018) - Caperchione, Cristina M.; Vandelanotte, Corneel; Corry, Kelly; Power, Deborah; Gill, Nina; Duncan, Mitch J.
Abstract : Objective: Despite the benefits associated with workplace health programs, many organizations are unable to offer them due to financial constraints. To address this barrier, the existing 10, 000 Steps program trialed the 10, 000 Steps Pedometer Microgrant Scheme. This study assessed the feasibility and acceptability of the Microgrant Scheme. Methods: Semi-structured interviews with employee representatives ( n  = 19) were used to explore perceptions of the Microgrant Scheme. Thematic inductive analysis was conducted. Results: Three main themes emerged: 1) the need for workplace initiatives to address health promotion issues ( The Need ); 2) the factors associated with the application and implementation process ( The Process ); and 3) employee and employer benefits associated with the Microgrant Scheme ( The Outcomes ). Conclusion: These findings highlight the potential utility of a Microgrant Scheme to extend the reach and long-term sustainability of workplace health promotion activities.